2010
DOI: 10.2478/v10153-010-0043-9
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation in Patients with Colorectal Cancer - Correlation with Some Clinical and Morphological Features and with Local Tumour Invasion

Abstract: Tumours with microsatellite instability, high level methylation and CIMP have distinctive clinical and morphological features. The level of hMLH1 and TIMP3 methylation and CIMP status can be correlated with the local tumour invasion. Different mechanisms, even for one and the same patient, can be responsible for the development of more than one third of the synchronous polyps and carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The CIMP CRC subtype associates with a high frequency of CpG hypermethylation and is diagnosed based on the methylation status of various genes that participate in regulation of calcium transport ( CACNA1G ), proliferation ( IGF2 ), Wnt signaling ( NEUROG1 ), transcription activity ( RUNX3 ), and suppression of cytokine signaling ( 124 , 125 ). Hypermethylation of MLH1 involved in DNA mismatch repair, and TIMP3 , which inhibits metalloproteinases, also associate with the CIMP phenotype ( 126 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CIMP CRC subtype associates with a high frequency of CpG hypermethylation and is diagnosed based on the methylation status of various genes that participate in regulation of calcium transport ( CACNA1G ), proliferation ( IGF2 ), Wnt signaling ( NEUROG1 ), transcription activity ( RUNX3 ), and suppression of cytokine signaling ( 124 , 125 ). Hypermethylation of MLH1 involved in DNA mismatch repair, and TIMP3 , which inhibits metalloproteinases, also associate with the CIMP phenotype ( 126 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, hypomethylation of the transposable DNA element long interspersed nuclear element-1 has been shown to activate the MET, RAB3IP , and CHRM3 proto-oncogenes in CRC metastases ( 136 ). Mirchev et al characterized the association between DNA methylation status of the MLH1, p16 INK , TIMP3 , and TPEF genes and various clinicomorphological features of CRC ( 126 ). These investigators reported hypermethylation of MLH1 and p16 INK in elderly patients; MLH1, p16 INK , and TIMP3 in proximal tumors; and p16 INK in poorly differentiated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Since its postulation by Toyota et al in 1999 [74], current investigations have increasingly focused on what is known as the CpG island methylator phenotype (CIMP) of tumor suppressor genes involved in CRC. More recent studies have revealed that numerous genes are hypermethylated at their promoter regions and silenced in CRC [75-78]. These include regulators of DNA mismatch repair such as MLH1 and MGMT (O 6 -methylguanine-DNA methyltransferase), and negative regulators of Wnt signaling such as Wnt inhibitory factor 1 ( WIF1 ) [79].…”
Section: Dna Methylationmentioning
confidence: 99%
“…F. nucleatum was also found concerning DNA methylation by targeting innate immune signaling [187]. Several investigations of CRC epigenome have introduced numerous aberrant methylated genes in CRC cases, such as RAAS F2A , WIF1 , ALX4 , MGM2 , APC , RUNX3 , p14 , p16 , SOX2 , and NDRG4 [188,189,190]. It is noteworthy that aberrant methylation of cMyc gene, encoding the c-myc oncoprotein, has been detected in CRC cases [191].…”
Section: The Role Of Bacterial Metabolites In Epigenetic Modificatmentioning
confidence: 99%